Optical impedance matching studied with Scanning Near-Field Optical Microscopy - Gademann, Anselm (Trinity College (Dublin, Ireland). School of Physics, 2003)
This thesis is a study of reflection-mode Scanning Near-Field Optical Microscopy (SNOM). A microscope was built for non-invasive imaging of samples, with optical resolutions better than the diffraction limit. The microscope also incorporates a mechanism for imaging the topography of a sample with a resolution better than 30 nm. The newly implemented shear-force system is based on a tuning fork method and therefore does not rely on an additional laser close to the tip apex. The design of the SNOM and of a fibre pulling machine for producing optical fibre tips will be presented, along with results obtained on test, calibration and transmission line samples.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin